Could Marginal Adaptation of Composite Resin Restorations Be Influenced by a Different Polymer Using Different Techniques? - Pereira, Jefferson Ricardo; Vermudt, Alef; Junior, Ageu Raupp; Bordignon, Diego Saccon; Medeiros, Henrique Vieira; Galvani, Lucas David [UNESP]; Rosa, Ricardo Abreu da; Só, Marcus Vinicius Reis; Kuga, Milton Carlos [UNESP] (MDPI, 2024)
Background: Marginal adaptation is one of biggest challenges in restorative dentistry, mainly in restoration of composite resin. Even with development of lower shrinkage materials, like those which use the polymer silorane, it is necessary a faithful clinical protocol in order to obtain better results and more clinical durability of restorative procedure. The purpose of this study was investigated if different polymers can influence on marginal adaptation of different composite resin restorations. Material and methods: Twenty class V cavities were confectioned in twenty human molars in a standardized way. Ten dentists received one tooth each and a questionnaire to describe their own clinical protocol. The other 10 teeth were restored by one researcher as control group. The cavities received the adhesive system than increments of composite resin, and so the restorations were finished with finishing bur (KG Sorensen, São Paulo, SP, Brazil) to remove the excess, followed by sof-lex discs (3M ESPE). After this stage, all of specimens were embedded in 1% Methylene blue (Prolabo, Paris, France) during 48 h. The evaluation of pigment penetration into the interfaces was performed after specimens were washed in distilled water and longitudinally sectioned with steel Diamond disc in low velocity. Results: There was significant statistical difference between the different techniques using compose resin. Conclusions: it was possible conclude that the clinical protocol to perform dental restoration interfere dramatically in the final results of restorative procedure.
Keywords: bisgma; composite resin; dental materials; dental restoration; marginal adaptation; polymers; silorane